Suicides in degenerative neurocognitive disorders and traumatic brain injuries - Tiina Talaslahti; Milena Ginters; Anniina Palm; Hannu Kautiainen; Risto Vataja; Henrik Elonheimo; Jaana Suvisaari; Hannu Koponen; Nina Lindberg (European Psychiatry, 2024)
Abstract